Nonlinear adaptive sliding-mode control of the electronically controlled air suspension system. (17th October 2019) - Rui, Bai
Recent years, electronically controlled air suspension has been widely used in vehicles to improve the riding comfort and the road holding ability. This article presents a new nonlinear adaptive sliding-mode control method for electronically controlled air suspension. A nonlinear dynamical model of electronically controlled air suspension is established, where the nonlinear dynamical characteristic of the air spring is considered. Based on the proposed nonlinear dynamic model, an adaptive sliding-mode control method is presented to stabilize the displacement of electronically controlled air suspension in the presence of parameter uncertainties. Parameter adaptive laws are designed to estimate the unknown parameters in electronically controlled air suspension. Stability analysis of the proposed nonlinear adaptive sliding-mode control method is given using Lyapunov stability theory. At last, the reliability of the proposed control method is evaluated by the computer simulation. Simulation research shows that the proposed control method can obtain the satisfactory control performance for electronically controlled air suspension.